2019
DOI: 10.1121/1.5134770
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of round-window stimulation of the cochlea in patients with stapedial otosclerosis

Abstract: An active actuator coupled to the round window (RW) can transmit mechanical vibrations into the cochlea and has become a therapeutic option of hearing rehabilitation for patients with stapedial otosclerosis. A finite-element model of the human ear that includes sound transmission effects of the vestibular and cochlear aqueducts of the inner ear is adopted in this study for investigating the cochlear response to RW stimulation under stapes fixation. There are two effects due to otosclerosis of the stapes: the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…Therefore, it is necessary to analyze the influence of these typical types of middle-ear disorder on reverse stimulation under the influence of coupling effects of actuator and RWM. According to the predicted results of the model about otosclerosis, it can be found that otosclerosis causes the reverse stimulation’s performance to decrease to varying degrees, which is similar to the change trend of | P SV P ST | predicted by the finite-element model of Zhang et al 19 The resonance response of the coupling impedance model of the human ear and the actuator based on reverse pressure transfer function referenced to actuator velocity is consistent with the impedance model of the human ear based on reverse pressure transfer function referenced to actuator pressure. 45 In contrast, the ossicular chain disarticulation reduces the middle-ear load impedance during reverse stimulation, which slightly improves the reverse stimulation’s performance.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Therefore, it is necessary to analyze the influence of these typical types of middle-ear disorder on reverse stimulation under the influence of coupling effects of actuator and RWM. According to the predicted results of the model about otosclerosis, it can be found that otosclerosis causes the reverse stimulation’s performance to decrease to varying degrees, which is similar to the change trend of | P SV P ST | predicted by the finite-element model of Zhang et al 19 The resonance response of the coupling impedance model of the human ear and the actuator based on reverse pressure transfer function referenced to actuator velocity is consistent with the impedance model of the human ear based on reverse pressure transfer function referenced to actuator pressure. 45 In contrast, the ossicular chain disarticulation reduces the middle-ear load impedance during reverse stimulation, which slightly improves the reverse stimulation’s performance.…”
Section: Discussionsupporting
confidence: 79%
“…Since the reverse stimulation is used for treating conductive or mixed hearing loss, the inefficient coupling’s influence in the ear with middle-ear disorder was also investigated by simulating two typical forms of middle-ear disorder: otosclerosis and ossicular chain disarticulation. 19,41 Otosclerosis prevents sound energy into the inner ear, and its typical physiological changes are the hardening of the stapedial annular ligament and the increase in the stapes mass. Hardening of the stapedial annular ligament was simulated by changing its stiffness to 10 times or 100 times the normal value.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations